PENGALAMAN PERAWAT DALAM PEMBERIAN ASUHAN KEPERAWATAN SPIRITUAL DI RUANG RAWAT INAP - Herman Priyono Luawo; Nuridah Nuridah (Jurnal Endurance, 2023)
Nurses have a very big role in fulfilling basic human needs holistically, including meeting the spiritual needs of patients. However, applying it requires high consistency in meeting the patient's spiritual needs during the treatment period. This study aims to explore the experiences of nurses in carrying out spiritual nursing care in inpatient rooms. This research method uses interview techniques using structured interview guidelines where the sample obtained is 8 people. The results of this study found 3 themes namely: the understanding of nurses in providing spiritual care, the benefits of providing spiritual care, and the role of nurses in providing spiritual care. Support and development efforts are needed in carrying out spiritual nursing care in health services to increase the understanding of nurses and the active role of nurses to be more optimal so that patients have satisfaction in health services, especially in fulfilling their spiritual needs.